Sub-regional hippocampal volumes in first-episode drug-naïve major depression disorder. (15th October 2021) - Liu, Mu-N; Pantouw, Jakobus Gerick; Yang, Kai-Chun; Hu, Li-Yu; Liou, Ying-Jay; Lirng, Jiing-Feng; Chou, Yuan-Hwa
Highlights: Investigation on sub-regional hippocampal volumes in first-episode drug-naïve MDD patients. We used manual and automatic segmentation methods of hippocampus. Smaller hippocampal head volumes in MDD patients compared to healthy controls. Higher magnitude of CA4/DG asymmetry in MDD patients compared to healthy controls. A trend of negative correlation between left head volume and depressive severity. Abstract: Hippocampal volume reduction was reported to underlie depressive symptomatology, however, the evidence to date remains inconsistent. For the complex intrinsic organization of hippocampus, the hippocampal volumes can be further divided into subfields or axial parts. The current study aimed to explore the alterations of hippocampal sub-regional volumes in first episode drug-naïve major depressive disorder (MDD) by two segmentation methods. Thirty-five first-episode drug-naïve MDD and 35 age- and gender-matched healthy controls (HC) were recruited. Volumes of three sub-regions of hippocampus along the longitudinal axis (head, body and tail) were analyzed manually and eight transverse subfields were automatically determined using FreeSurfer. An asymmetric index (AI) of volumes was defined as (∣Left − Right∣/∣Left + Right∣) * 100. There were significant reductions in the volumes of bilateral hippocampal head in MDD compared to HC. The volumes of eight subfields were not different between groups. MDD patients had higher AI values in the subfield of cornu ammonis 4/dentate gyrus than HC. The change in hippocampal sub-regional volumes might be an imaging biomarker in the first-episode, drug-naïve patients with MDD. Current findings may contribute to developing new diagnostic and therapeutic strategies for major depression.